Local public administration reform to the protection of fundamental rights in the XXI century - Reyna, Justo José (Universidad Nacional del Litoral, 2015)
This paper makes two proposals for local public administration regarding the need to reform the tutelage of minimal or existential core of the fundamental rights of the human person. We propose, first, the creation of local organizational units so that they act in the field of endonational intergoverment with other governments, other levels such as the Provincial Public Administration and the National Public Administration. The paper complements another one, which identifies the "constitutional principle of joint action for the protection of fundamental rights". It is proposed, on the other hand, it is the local level that encourages the public management to generate an organizational or multidimensional space of intergovernment, so that all endonational public subjects (national, provincial and local government) assume their responsibility of implementing the core of minimum or basic fundamental rights of the human person.